2012
DOI: 10.1186/1710-1492-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune markers in serum during gestation and in breast milk and the risk of asthma-like symptoms at ages 6 and 12 months: a longitudinal study

Abstract: BackgroundThe role of breast milk on the risk of childhood asthma is in dispute. The aim of this prospective study is to determine the relationship of immune markers in maternal serum during gestation and breast milk to asthma-like symptoms (AS) in infancy.MethodsPregnant women were recruited in Columbia and Charleston, South Carolina. Blood (median: three weeks before delivery) and breast milk (three weeks after delivery) samples were collected. Concentrations of interferon (IFN)-γ, IFN gamma-induced protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 52 publications
1
57
2
2
Order By: Relevance
“…Immune markers IL-12 (p70), IL-4, IL-10, IL-1β, and CCL11 (eotaxin) in whey were not considered in the statistical analyses because high proportions of nondetectable values (low or undetectable concentrations) were obtained (14). Immune markers IL-5 and IL-13 showed low concentrations in whey (geometric mean: 0.12 and 0.19 pg/ml respectively; Table 2), whereas IgA, interferon (IFN)-γ-induced protein 10 (IP-10 or CXCL10), and TGF-β1 showed higher concentrations than other immune markers (geometric mean: 12.97 mg/ml, 141.25 pg/ml, and 469.21 pg/ml, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune markers IL-12 (p70), IL-4, IL-10, IL-1β, and CCL11 (eotaxin) in whey were not considered in the statistical analyses because high proportions of nondetectable values (low or undetectable concentrations) were obtained (14). Immune markers IL-5 and IL-13 showed low concentrations in whey (geometric mean: 0.12 and 0.19 pg/ml respectively; Table 2), whereas IgA, interferon (IFN)-γ-induced protein 10 (IP-10 or CXCL10), and TGF-β1 showed higher concentrations than other immune markers (geometric mean: 12.97 mg/ml, 141.25 pg/ml, and 469.21 pg/ml, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, our data showed only that IL-5 was higher if the mother had a history of asthma (0.28 compared with 0.08 pg/ml). Recently, we reported that higher whey levels of IL-5 were a risk for asthmalike symptoms in children at ages of 6 and 12 mo (14). Thus, maternal history of asthma may partially contribute to the risk of asthma by increasing IL-5 levels in breast milk (history of maternal asthma → IL-5 in whey → asthma-like symptoms).…”
Section: Maternal Characteristics and Other Child's Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study showed that the levels of soluble CD14, total IgA and transforming growth factor-β1 (TGF-β1) in breast milk at either day 7 or day 28 are not associated with subsequent development of eczema or atopic sensitization during the first year of life (38) . Similarly, but not totally, another study reported that maternal serum and whey levels of IL-5 and IL-13 are risk markers for asthma-like symptoms, whereas whey IgA and TGF-β1 seem to have a protective effect during infancy (13) . The composition of human milk can be affected by the diet of lactating women (39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that breast-feeding, including EBF, predominant breast-feeding for at least 6 months and partial breast-feeding for up to 1 year, may reduce the risk of diarrhoea, respiratory illness and other common diseases in infants (4)(5)(6)(7)(8)(9) . However, for allergic diseases, such as wheezing/asthma, eczema, allergic rhinitis and atopic dermatitis, whether breast-feeding is protective or a risk remains controversial (10)(11)(12)(13) . In China, previous studies have investigated the association of feeding pattern and different infant illnesses.…”
mentioning
confidence: 99%